2018
DOI: 10.3390/nu10070882
|View full text |Cite
|
Sign up to set email alerts
|

Chrysin Inhibits Advanced Glycation End Products-Induced Kidney Fibrosis in Renal Mesangial Cells and Diabetic Kidneys

Abstract: Advanced glycation end products (AGEs) play a causative role in the development of diabetic nephropathy via induction of matrix protein deposition in kidneys. This study investigated inhibitory effects of chrysin, present in bee propolis and herbs, on glomerulosclerosis in db/db mice and AGEs-exposed renal mesangial cells. The in vivo study explored the demoting effects of 10 mg/kg chrysin on glomerular fibrosis in a type 2 diabetic model. Oral supplementation of chrysin inhibited the collagen fiber accumulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 46 publications
(75 reference statements)
1
33
0
Order By: Relevance
“…Based on the previous observations, we further suggested that mUC-MSC paracrine significantly inhibited mesangial cell proliferation and activation of the PI3K/Akt and MAPK signaling pathways (Figures 4(a) and 4(b)). In addition to causing EMT, EndoMT, and MFT, TGF-β1 also promotes the deposition of ECM proteins by directly inhibiting the activity of MMPs and eliciting glomerular basement membrane thickening and mesangial expansion [47][48][49][50]. Herein, we investigated the role of mUC-MSC paracrine in regulating the expression of MMPs, and found that MSC-CM could elevate the levels of MMP2 and MMP9 in mesangial cells cultured in HG (Figure 4(c)), which is in accordance with a recent study showing that the upregulation of MMP9 is related to the attenuation of bone marrow-derived MSCs for DN in diabetic rats [19].…”
Section: Journal Of Diabetes Researchmentioning
confidence: 99%
“…Based on the previous observations, we further suggested that mUC-MSC paracrine significantly inhibited mesangial cell proliferation and activation of the PI3K/Akt and MAPK signaling pathways (Figures 4(a) and 4(b)). In addition to causing EMT, EndoMT, and MFT, TGF-β1 also promotes the deposition of ECM proteins by directly inhibiting the activity of MMPs and eliciting glomerular basement membrane thickening and mesangial expansion [47][48][49][50]. Herein, we investigated the role of mUC-MSC paracrine in regulating the expression of MMPs, and found that MSC-CM could elevate the levels of MMP2 and MMP9 in mesangial cells cultured in HG (Figure 4(c)), which is in accordance with a recent study showing that the upregulation of MMP9 is related to the attenuation of bone marrow-derived MSCs for DN in diabetic rats [19].…”
Section: Journal Of Diabetes Researchmentioning
confidence: 99%
“…Hou et al demonstrated that Salvianolic acid A prevented from diabetic nephropathy by restraining AGE-RAGE-NOX4 with validated safety for the first time [19], which dramatically accelerated the advances of drug discovery since myriad compounds concerning AGE-RAGE inhibition and diabetic nephropathy regression had been withdrawn from clinical trials due to its unsatisfactory safety [130]. Resveratrol [131,132], kaempferitrin [133] and chrysin [134] could reduce renal damage through AGE/RAGE or Nrf2-Keap1 in animal models of diabetic nephropathy. Additionally, resveratrol also played paramount roles in protecting against diabetic renal fibrosis [135], aging kidney [66] and kidney damage [136,137] in animal models.…”
Section: Therapeutic Opportunities For Natural Products In Aging Kidnmentioning
confidence: 99%
“…Moreover, this flavonoid prevented the increase in collagen IV and TGF-β1 levels [75]. The anti-fibrotic effect has also been demonstrated by other flavonoids such as chrysin which inhibited AGEs-induced expression of collagens, and matrix metalloproteinases in mesangial cells and prevented collagen and AGEs accumulation in diabetic kidneys from the db/db mouse model of T2D [77].…”
Section: Diabetic Nephropathymentioning
confidence: 77%